PRINSIP BEBAS-AKTIF INDONESIA PADA PRESIDENSI G20 TAHUN 2022 - Azmi, Agus Nilmada; Bintang, Raisya (Emerald: Journal of Economics and Social Sciences, 2024)
The Indonesian Ministry of Foreign Affairs revealed that the polarization of the international structure and the conflict between Russia and Ukraine in January 2022 have become challenges in gaining consensus on various commitments for Indonesia's G20 presidency in 2022. The conflict also has the potential to reduce soft power in an attempt to build branding to achieve national interests. This research uses a literature study method through the analysis of foreign policy documents, official speeches, and various supporting documents that explain the steps implemented by the Indonesian government in the G20 Presidency. In the G20 Presidency, Indonesia applied the principle of free and active (Bebas- Aktif) in embracing every group, handling the Russian-Ukrainian conflict, and achieving various national interests. During the G20 Presidency, Indonesia also implemented a multilateral approach in order to promote regional stability by paying attention to cross-security issues and peace efforts. The implementation of the free-active principle in the G20 Presidency aims to fulfill Indonesia's national interest in the welfare of society.